2021
DOI: 10.1002/anie.202101445
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Diboration of Spirocyclobutenes: A Platform for the Synthesis of Spirocycles with Orthogonal Exit Vectors

Abstract: The diastereo‐ and enantioselective diboration of spirocyclobutenes provides a platform for the rapid preparation of a wide variety of chiral spirocyclic building blocks. The chemoselective functionalization of the carbon‐boron bond in the products, including a stereospecific sp3‐sp2 Suzuki–Miyaura cross‐coupling reaction, provides a powerful tool to control the directionality and the nature of the exit vectors in the spirocyclic framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…4,5 Most existing catalytic asymmetric approaches for cyclobutane synthesis rely either on ring-closure, [6][7][8][9][10][11][12][13] or the functionalization of pre-formed four-membered rings using activating or directing groups. [14][15][16] Direct addition reactions to unactivated cyclobutenes are rare, [17][18][19] but attractive as they offer a modular entry to functionalized cyclobutanes and are generally not limited to specic substitution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Most existing catalytic asymmetric approaches for cyclobutane synthesis rely either on ring-closure, [6][7][8][9][10][11][12][13] or the functionalization of pre-formed four-membered rings using activating or directing groups. [14][15][16] Direct addition reactions to unactivated cyclobutenes are rare, [17][18][19] but attractive as they offer a modular entry to functionalized cyclobutanes and are generally not limited to specic substitution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…With this idea, we recently developed the diboration of spirocyclobutenes I promoted by a Lewis base or a platinum catalyst ( Scheme 1 , a). 6 …”
mentioning
confidence: 99%
“…With this idea, we recently developed the diboration of spirocyclobutenes I promoted by a Lewis base or a platinum catalyst (Scheme 1, a). 6 Selective functionalization of the two boryl moieties in the products allowed us to prepare a wide array of spirocyclic building blocks, 2,3-disubstituted, with control in the nature and the directionality of the substituents in the cyclobutane ring. One of the limitations that we found was the inability to monofunctionalize the double bond using this approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We envision that application of the principles learned to the challenge of spirocyclic cyclobutene functionalization would provide an enabling tool for the creation of rigid and complex saturated carbo- and heterocycles. During the course of our studies, Tortosa and co-workers reported an elegant approach toward spirocyclic cyclobutene functionalization that involved a diboration followed by regioselective cross coupling of the less sterically encumbered C–B bond. , This two-step approach enabled the synthesis of many complex molecules. In this manuscript, a one-step process for arylboration of substituted spirocyclic cyclobutenes is presented, wherein two catalytic systems are utilized to achieve broad scope.…”
mentioning
confidence: 99%